Determinación de los costos de producción para una vivienda de emergencia para la fundación “Un techo para mi país” Ecuador - Haro Urrutia, Cristóbal Patricio (2014)
This work has been developed in order to determine production costs for emergency housing for the foundation "Un Techo Para Mi País" Ecuador. The issue in question is developed in 3 chapters and conclusion respectively. Each of the chapters is supported by information and actual field experience, which has allowed me to develop this work knowingly limit.